The Entrepreneurial perception of the small enterprise environment - P. Tomski; E. Wysłocka (Global Journal of Environmental Science and Management)
The way of perceiving the environment is the factor informing on the condition of the environment and its impact on the operation of enterprises whereas the impact on the operation is the factor determining how enterprises operate in realities where there is no place for atomized actions of isolated enterprises and the impact of the environment and relationships with its constituents and all forms of inter-organizational and interpersonal relationships are of increasingly critical importance. The objective of the study is to analyze the perception of the environment in which modern small enterprises operate. The study question relating to this problem was formulated as follows: 1) what is the perception of the environment by the entrepreneurs representing small enterprises? 2) Is the environment of small enterprises perceived as unfriendly (dynamically changing, hostile, heterogeneous) by them? The research tool was the questionnaire. The statistical analyses were conducted using the R Package. While summing up the results of the conducted research, it should be concluded that, in most studies in the field of management of modern enterprises, a frequent observation is defining the environment as turbulent or ultrafast. The perception of the entrepreneurs under research indicates, however, a slightly different, more lenient approach to the environment. Although they were not directly asked about the level of turbulence of the environment, the obtained results, maintaining the characteristics of the environment in the middle of the scales (dynamism, hostility, heterogeneity) indicate that this environment is not perceived in a drastic and pessimistic manner.